The Effect Of Online Learning Service Quality On Student Satisfaction During COVID19 Pandemic In 2020 - Hery Winoto Tj; Hans Harischandra Tanuraharjo (Jurnal Manajemen Indonesia, 2020)
The coronavirus disease in 2019 (COVID 19) becomes the focus of all the countries in the world to finish. This virus is so dangerous that all efforts get done to stop it. Unfortunately, it is impossible to do it, but what can do is by the prevention of its spread. To do it, moreover, the government of Indonesia advises all Indonesians to work from home in all sectors, including education. As one of the responsible higher institutions for educating the students, Universitas Kristen Krida Wacana obeys this suggestion by the work from home for the lecturers to carry on online learning for the students. This study intends to investigate and analyze the online learning quality on the satisfaction of the management students in the faculty of economics and business, taking the subject of human resource management and organizational behavior in 2020. Furthermore, they become the population of this study. By the stratified random sampling method from the community consisting of 76 students and a variance-based structural equation model (SEM), this research grabs 64 students as the sample. It analyzes the collected data associated with latent variables. After testing and analyzing the data, this study infers that the better quality of service online learning, the more satisfied the students. In other words, the implementation of this online learning is successful. Likewise, some practical and theoretical recommendations based on this evidence are available. Keywords – lecturer, online learning service quality; the spread of COVID 19; student satisfaction; work from home